Maximizing Productivity: The Power of Standard Operating Procedure, Work Environment and Communication - Afriza, Banyu Raul (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Without good HR management, growth, progress, and achievement of company goals will be difficult to achieve, so companies are required to manage HR appropriately considering the large role of HR in a company and because HR will determine a lot related to company productivity. The purpose of this study is to determine the effect of standard operating procedures, work environment and communication together on work productivity at PT. Pesonna Optima Jasa in Central Jakarta. This research was designed using a descriptive method with a quantitative approach. The population in this study was 131 employees at PT. Pesonna Optima Jasa in Central Jakarta. The sampling technique was saturated, so samples were taken as many as 131 employees. The results of this study show that there is a positive and significant influence between Standard Operating Procedures, Work Environment and Communication on Work Productivity. This can be proven by the magnitude of Fcalculate (44.863 > 2.44) with significant (0.000 < 0.05). The magnitude of the contribution of the influence of Standard Operating Procedures, Work Environment and Communication together on Work Productivity (Y) is 51.5%.